2012
DOI: 10.1128/jvi.01427-12
|View full text |Cite
|
Sign up to set email alerts
|

Acute Diarrhea in West African Children: Diverse Enteric Viruses and a Novel Parvovirus Genus

Abstract: g Parvoviruses cause a variety of mild to severe symptoms or asymptomatic infections in humans and animals. During a viral metagenomic analysis of feces from children with acute diarrhea in Burkina Faso, we identified in decreasing prevalence nucleic acids from anelloviruses, dependoviruses, sapoviruses, enteroviruses, bocaviruses, noroviruses, adenoviruses, parechoviruses, rotaviruses, cosavirus, astroviruses, and hepatitis B virus. Sequences from a highly divergent parvovirus, provisionally called bufavirus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
147
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(158 citation statements)
references
References 74 publications
(83 reference statements)
7
147
0
4
Order By: Relevance
“…Based on an alignment with reference bufavirus sequences, the genome (KU867071) was predicted to encode a partial NS1 (579 aa), a putative protein (129 aa) and partial structural proteins VP1 (679 aa) and VP2 (538 aa). Expression of VP1 was likely due to an alternative splicing mechanism, as described previously (Phan et al, 2012). Comparative analysis of the near-complete genome sequence showed that the Austrian porcine bufavirus (KU867071) shared a similarity of 65.9 % to human bufavirus-1 BF7 (JX027295), 65.7 % to human bufavirus-2 BF39 (JX027297), 65.4 % to human bufavirus-3 AHP178 (AB982217), 93 % to porcine bufavirus Swine/Zsana/2013/ HUN (KT965075), 58.4 % to Shrew ZM38 (AB937988), The newly determined sequence is denoted by a filled square.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Based on an alignment with reference bufavirus sequences, the genome (KU867071) was predicted to encode a partial NS1 (579 aa), a putative protein (129 aa) and partial structural proteins VP1 (679 aa) and VP2 (538 aa). Expression of VP1 was likely due to an alternative splicing mechanism, as described previously (Phan et al, 2012). Comparative analysis of the near-complete genome sequence showed that the Austrian porcine bufavirus (KU867071) shared a similarity of 65.9 % to human bufavirus-1 BF7 (JX027295), 65.7 % to human bufavirus-2 BF39 (JX027297), 65.4 % to human bufavirus-3 AHP178 (AB982217), 93 % to porcine bufavirus Swine/Zsana/2013/ HUN (KT965075), 58.4 % to Shrew ZM38 (AB937988), The newly determined sequence is denoted by a filled square.…”
mentioning
confidence: 64%
“…Genome comparison and phylogenetic analysis have grouped human bufaviruses into three genotypes (Yahiro et al, 2014). Bufavirus has first been identified in faeces of children with acute diarrhoea in Burkina Faso, a landlocked country in West Africa, and found in one Tunisian child (Phan et al, 2012). Subsequently, the virus has been discovered sporadically in cases of diarrhoea in Bhutan (Yahiro et al, 2014), Finland (V€ ais€ anen et al, 2014), the Netherlands (Smits et al, 2014), Turkey (Altay et al, 2015), Thailand (Chieochansin et al, 2015) and China (Huang et al, 2015).…”
mentioning
confidence: 99%
“…Potential human pathogens that are still pending recognition include genetic variants of Human Bocavirus (HBoV 1 -4), which are particularly common in the respiratory and gastrointestinal tracts of children (Kapoor et al 2010;Kantola et al 2011), and two broadly distributed genotypes of a "PARV4"-based genus (the aforementioned Partetraviruses), parenterally transmitted among injecting drug users, hemophiliacs, and polytransfused individuals (Sharp et al 2009;Lahtinen et al 2011). Most recently, viruses from another potential genus, with sequences resembling both Parvoviruses and Amdoviruses, were detected in fecal samples from children in Burkina Faso, and tentatively named Bufaviruses (Phan et al 2012). In vitro culture systems or high titer clinical samples are often not available for new members, which can thus only be studied by PCR amplification from patient tissue.…”
mentioning
confidence: 99%
“…Вид Primate protoparvovirus 1 объединил бу-фавирусы человека (Bufavirus, BuV, BuPV), впер-вые обнаруженные в 2012 г. при проведении метагеномного анализа клинических образцов из Буркина-Фасо [62]. Известны три геноти-па буфавирусов: BuV1 (BuPV1a, BuPV1b), BuV2 (BuPV2) и BuV3 (BuPV3) [84].…”
Section: род Protoparvovirusunclassified
“…Диагностика может выполняться с помощью гнездовой ПЦР по NS1 области генома BuPV [62]. Вирусная на-грузка составляет 10 3 -10 4 копий ДНК/мл фе-кального супернатанта [77].…”
Section: род Protoparvovirusunclassified